(untitled) (International Journal of Physiotherapy, 2016)
Background: Hemiparetic and hemiplegic cerebral palsy(CP) constitute at least a third of all people with CP. Children with hemiparesis are suffering from weak hand muscles and retarded hand use.Mirror therapy is a relatively new approach in rehabilitation used in different neurological disorders. In mirror therapy a mirror is positioned orthogonally in front of the center of the patient’s body. The less-affected (healthy) extremity is moved and observed in the mirror. The purpose of this study was to determine the effect of mirror visual feedback on improving hand functions in children with hemiparesis. Methods: Forty children with hemiparesis of both sexes, ranged in age from five to seven years old, participated in this study. They were divided randomly into two groups of equal number (control and study). The control group received a specially designed physical therapy exercise program for four successive weeks while the study group received mirror exercise program in addition to the same program of the control group. Hand functions assessments was done using grasping and object manipulation subtests of Peabody developmental motor scale (PDMS-2). Evaluation was performed pre and post treatment program. Results:There was no significant difference between both groups in the pre-treatment mean values of all measured variables. Also, the results of this study revealed a significant improvement in the scores of the PDMS-2 andin grasp strength of the 2 groups. Post treatment results revealed more improvement in favor of the study group as compared with the control group. Conclusion: Using the mirror visual feedback could help in improving hand functions in children with hemiparesis.